2014
DOI: 10.1111/1365-2664.12293
|View full text |Cite
|
Sign up to set email alerts
|

Plant trait–digestibility relationships across management and climate gradients in permanent grasslands

Abstract: International audience1. Dry matter digestibility is a critical component of herbage nutritive value, a major service delivered by grasslands. The aim of this study was to test whether the dominance hypothesis applies to assess the impacts of environmental gradients and management regimes on thiscomponent of herbage nutritive value in permanent grasslands. 2. At the plant level, digestibility has been related to a number of functional traits, but whether this can be scaled up to the community level in species-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 46 publications
7
78
1
Order By: Relevance
“…lack generality) and (ii) are usually not useful for developing or managing diversified agroecosystems. For example, knowledge about grassland ecosystem services has greatly increased through the use of the "trait" approach (e.g., Gardarin et al 2014); however, stakeholders cannot use it for their own situations because it is too time consuming and requires specific skills. New research projects have been launched to bridge this gap through a simplified plant functional-group method .…”
Section: Limits Of Existing Tools For Supporting Biodiversity-based Amentioning
confidence: 99%
“…lack generality) and (ii) are usually not useful for developing or managing diversified agroecosystems. For example, knowledge about grassland ecosystem services has greatly increased through the use of the "trait" approach (e.g., Gardarin et al 2014); however, stakeholders cannot use it for their own situations because it is too time consuming and requires specific skills. New research projects have been launched to bridge this gap through a simplified plant functional-group method .…”
Section: Limits Of Existing Tools For Supporting Biodiversity-based Amentioning
confidence: 99%
“…Forage digestibility (2) and total nitrogen content (3) were measured on four 50 cm 9 50 cm vegetation samples per plot. Samples were mixed, dried for 72 h at 60°C, ground with a 0.5 mm grid, and then analyzed using Near InfraRed Spectrometry (Gardarin et al 2014). The other five agronomic properties were derived from the relative abundance of grass species.…”
Section: Agronomic Propertiesmentioning
confidence: 99%
“…This result suggests that management can partially decouple forage production from forage quality despite the higher potential of the most productive grasslands for forage associated with a short leaf lifespan index. This relative potential for decoupling production and quality may reflect a major influence of grass functional composition rather than a direct effect of management (Duru et al 2008;Gardarin et al 2014). Although Lavorel et al (2011) showed that forage quality decreased with extensification of management in mountain grasslands, we found no significant differences in forage quality between the different grassland types within hay meadows or pastures.…”
Section: Agronomic and Environmental Properties According To Managementmentioning
confidence: 99%
“…seasonal) duration (Jung et al, 2014;Lloret et al, 2012;Suding et al, 2008). Such changes in community plant traits can ultimately influence agronomic services such as forage yields and its nutritive value (Gardarin et al, 2014;Quétier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%